Analyses of the modifications in the pi circuits for inclusion of frequency influence in transmission line representation - Lessa, L. S. [UNESP]; Prado, A. J. [UNESP]; Bonelli, M. L. [UNESP]; Kurokawa, S. [UNESP]; Pissolato Filho, J.; Bovolato, L. F. [UNESP] (IEEE, 2011)
In this article, it is represented by state variables phase a transmission line which parameters are considered frequency independently and frequency dependent. It is analyzed what is the reasonable number of pi circuits and the number of blocks composed by parallel resistor and inductor in parallel for reduction of numerical oscillations. It is simulated the numerical routine with and without the effect of frequency in the longitudinal parameters. Initially, it is used state variables and pi circuits representing the transmission line composing a linear system which is solved by numerical routines based on the trapezoidal rule. The effect of frequency on the line is synthesized by resistors and inductors in parallel and this representation is analyzed in details. It is described transmission lines and the frequency influence in these lines through the state variables.
Keywords: Electromagnetic transient; EMTP; mathematical model; simulation; transmission lines; pi circuit; numeric method; wave traveling